Optimalisasi Tata Kelola Pemerintah Daerah untuk Meningkatkan Akuntabilitas dan Transparansi di Kelurahan Olak Kemang - Nela Safelia; Scheilla Aprilia Murnidayanti; Aegisia Sukmawati; Dahlia Dahlia; Afrizal Afrizal (Jurnal Pengabdian Masyarakat, 2025)
Urban villages hold crucial and strategic function in national development. Urban village is recognized as the smallest entity equivalent to a village. According to Government Regulation Number 73 of 2005 about Urban Village explains that urban village is led by “Lurah”. The leader of urban village has responsibility to manage the local resources, aiming to empower local community service, welfare, and foster self-sufficiency. To accomplish these goals, it requires professional local governance. However, there are still urban villages that indicate lack of adequate capacity to implement good governance in line with established standards. This research presents a community service program conducted by lecturers at accounting department, economic and business faculty in Jambi University, focusing local governance enhancement in Olak Kemang Urban Village, Jambi City. The main activities highlighted strengthening financial management and optimized digital tools to improve quality and effective communication with local community in Olak Kemang. According to the activities conducted showed that the urban village officials in Olak Kemang should enhance ability and skill in financial management and technology utilization, particularly optimize social media use. These initiatives are expected to foster greater accountability and transparency in financial management and public service within the urban village.